Incidence and risk factors of postoperative pancreatic fistula after pancreaticoduodenectomy: A large tertiary center experience - C. Tovikkai (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF Thailand| 2020 Objective: Pancreaticoduodenectomy (PD) is a major operation for the treatment of periampullary and pancreatic cancer, and the number of operations has increased in recent years. Postoperative pancreatic fistula (POPF) remains one of the important complications after PD. The present study aimed to analyze the incidence and risk factors of POPF. Materials and Methods: The clinical data of 227 patients who underwent PD in Siriraj Hospital between 2011 and 2016 were retrospectively reviewed. POPF was diagnosed and classified into three groups (grade A, B, or C) according to the International Study Group on Pancreatic Fistula (ISGPF). Clinically relevant pancreatic fistula (CR-POPF) takes into account only grade B or C. The risk factors of POPF after PD were analyzed. Univariate and multivariate logistic regression analyses were used to determine the risk factors correlated with POPF. Results: In total, 227 patients were included in this study. POPF occurred in 96 patients (42.3%), and these were classified into ISGPF grade A patients, 21 (9.3%); grade B, 54 (23.8%); and grade C, 21 (9.3%). The CR-POPF rate was 33.1%. Multivariate analysis revealed soft gland texture [Odds ratio (OR): 6.7, 95% confidence interval (CI): 1.5 to 30.9], small pancreatic duct (P-duct) diameter of <3 mm [OR: 4.6, 95% CI: 1.0 to 21.4], and a surgeon’s experience of <10 years [OR: 6.5, 95% CI: 1.4 to 30.6] were significant risk factors of POPF. Regarding CR-POPF, these three risk factors were also found to be statistically significant in the multivariate analysis. Conclusion: Even though the study involved a high volume center, the incidence of POPF after PD was still high, with ISGPF grade B the most common group. Soft gland texture, small P-duct diameter, and low surgeon experience were the key independent risk factors for both POPF and CR-POPF.